59 Racial disparities associated with increasing incidence of epithelial ovarian cancer in the United States. (13th November 2020) - Ratnaparkhi, R; Liao, C; Chan, A; Tian, C; Darcy, KM; Maxwell, L; Knapp, DS; Chan, JK
Abstract : Introduction: The incidence of ovarian cancer has decreased in the United States since the 1980s, predominantly driven by decreasing incidence in Non-Hispanic Whites. The purpose of this study was to identify racial disparities in histologic subtypes of epithelial ovarian cancer. Methods: Data were obtained from the United States Cancer Statistics (USCS) database from 2001 to 2016. Age-adjusted incidence per 100, 000 women and annual percent change (APC) in incidence were calculated using SEER*Stat and Joinpoint Software. Results: Of 319, 257 women diagnosed with epithelial ovarian cancer, 79.9% were Non-Hispanic White, 7.8% were Non-Hispanic Black, 7.9% were Hispanic, 3.5% were Asian/Pacific Islanders, and 0.9% were Other/Unknown. Over a sixteen-year period, the overall incidence of epithelial ovarian cancer decreased 1.96% per year (95% CI -2.13, -1.78, p < 0.001). However, in Non-Hispanic Blacks (APC 0.84%, 2.72%) and Asian/Pacific Islanders (APC 0.94%, 2.09%), the incidence of serous and clear cell carcinoma respectively have both increased significantly in the same period. Hispanics had a significant decrease only in incidence of endometrioid (-2.1%) and mucinous (-4.23%) histologies (figure 1 ). This contrasts the decrease in incidence for Non-Hispanic Whites seen across all histologic subtypes. Conclusions: Persistent racial disparities are unmasked when analyzing trends in ovarian cancer incidence by histologic subtype. Non-Hispanic Blacks and Asian/Pacific Islanders continue to have an increasing incidence of serous and clear cell ovarian carcinomas.